Tanggung Jawab Notaris Terhadap Akta Autentik yang Dibatalkan oleh Pengadilan atas Permintaan Para Pihak - Tresta Viana Dhiya Ulhaq Taofik; Mohamad Fajri Mekka Putra (Syntax Idea)
The purpose of this study was to find out about Notary’s responsibility and its legal consequences towards authentic deeds that has been canceled by the court upon the parties’s request. The method that used in this study is study of literature. The data collection tool implemented in this study was a mechanism for collecting legal materials by searching for literature and other information using online searches via the internet and offline through books and journals to complete this research. The research of this study shows that Notary’s responsibility that has ben cancelled by the court is based on Law Number 2 of 2014 concerning amendments to Law Number 30 of 2014 concerning Notary Position towards material evidentiary inside the authentic deeds that has been made by the Notary and its legal consequences on the authentic deeds if the authentic deeds does not meet the requirements regarding the form, is canceled in court against the cancellation of the deed issued by a Notary, which results in a deed being null and void by law.